2016
DOI: 10.1093/ee/nvw118
|View full text |Cite
|
Sign up to set email alerts
|

Using Global and Regional Species Distribution Models (SDM) to Infer the Invasive Stage ofLatrodectus geometricus(Araneae: Theridiidae) in the Americas

Abstract: The brown widow spider, Latrodectus geometricus C. L. Koch, 1841, is a large spider of the family Theridiidae that belongs to a genus of medical interest owing to its potent neurotoxic venom, which causes severe pain in humans. In America, this alien spider has been found in virtually all countries in the region, mainly associated with human dwellings, but also in agricultural sectors. However, the invasive process and potential distribution of this invasive species across the American continent are completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 46 publications
1
37
0
1
Order By: Relevance
“…Species distribution models (SDMs) could be used to predict the potential distribution of an invasive species assuming that climatic niches do not change [niche conservatism sensu (Wiens & Graham, )] and also to hypothesize stages and the dynamic of invasions (Gallien et al ., ; Taucare‐Ríos et al ., ). Such models can be defined as ‘statistical methods that combine observations of species occurrence with environmental variables’, and have been used to predict potential distributions, especially in invasive species (Elith & Leathwick, ; Vink et al ., ; Kumar et al ., ; Taucare‐Ríos et al ., ). All studies, in which invasion ranges can be predicted with ocurrences from the native range, assume niche conservatism in alien species (Peterson & Vieglais, ; Broennimann et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Species distribution models (SDMs) could be used to predict the potential distribution of an invasive species assuming that climatic niches do not change [niche conservatism sensu (Wiens & Graham, )] and also to hypothesize stages and the dynamic of invasions (Gallien et al ., ; Taucare‐Ríos et al ., ). Such models can be defined as ‘statistical methods that combine observations of species occurrence with environmental variables’, and have been used to predict potential distributions, especially in invasive species (Elith & Leathwick, ; Vink et al ., ; Kumar et al ., ; Taucare‐Ríos et al ., ). All studies, in which invasion ranges can be predicted with ocurrences from the native range, assume niche conservatism in alien species (Peterson & Vieglais, ; Broennimann et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Making comparisons between global and regional SDMs can be a good method of inferring invasion processes (Gallien et al ., ) and has already been used to analyse the invasion of alien spiders (Taucare‐Ríos et al ., ). Initially the global model was constructed by using all occurrences collected for the species worldwide and could be viewed as a proxy of the species' fundamental niche (Vetaas, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Esto significa proyectar en el espacio geográfico (SDM) una estimación de los requerimientos ambientales de una especie (ENM), los que se aproximan al nicho fundamental o al nicho realizado dependiendo del método (Soberón et al 2017). Los SDM se han usado en Chile para conocer la distribución potencial de artrópodos tanto alóctonos (Estay et al 2014;Taucare-Ríos et al 2016;Alaniz et al 2017Alaniz et al , 2018Carvajal et al 2018) como autóctonos (Canals et al 2016Taucare-Ríos 2017;Alaniz et al 2018;Taucare-Ríos y Cerpa 2018).…”
Section: Introductionunclassified
“…SDMs have been successfully used in studies concerning invasive species, one of the main components of the human‐driven global environmental change (Jeschke et al ., ; Hulme, ; Dyer et al ., ). Several studies reported the high predictive accuracy of SDMs in estimating potential areas of alien species invasion (Stohlgren & Schnase, ; Crall et al ., ; Mori et al ., ; Taucare‐Ríos, Bizama & Bustamante, ; but see Buchadas et al ., ). Spatially explicit models are also useful tools to investigate the response of animal species to habitat change at the population level; conversely, building them at large spatial scales or for many taxa is challenging and may produce unreliable outputs (Dunning et al ., ; Chandler & Clark, ).…”
Section: Introductionmentioning
confidence: 99%